Improving Speaking Ability Through Show and Tell for Eighth Graders - Nizam; Mukrim; Mashuri; Kamaruddin, Abd. (LPPM Universitas Advent Indonesia, 2026)
This study aims to investigate the effect of Show and Tell on students’ Speaking Ability particularly in accuracy and comprehensibility at The Eighth Grade Students of SMP Negeri Satu Atap Lik Layana Indah in Academic Year 2024/2025. This study used a quantitative approach with a Pre-experimental design using one group pre-test post-test design. In this research, the researcher used a total sampling technique with a total of sample 32 students. To analyze the data, the researcher used statistical computation by using SPSS software. After implementing Show and Tell method over six meetings, a post-test was administered to measure improvements. The results show that the mean of the pre-test score was 43.75, while the mean score of the post-test increased to 58.59, demonstrating a significant improvement. After getting the mean score the researcher performed a normality test, which showed the data were not normally distributed. Therefore, the researcher applied the Wilcoxon Signed Rank Test. The result of the test shows a significance value (Asymp. Sig. 2-tailed) is .000, which is smaller than 0.05, indicating a significant improvement in students’ speaking ability after using the show and tell method, confirming that the hypothesis (Ha) is accepted. Thus, the use of Show and Tell Method is effective in improving students’ speaking ability in terms of accuracy and comprehensibility of eight-grade students’ at SMP Negeri Satu Atap Lik Layana Indah.